PRODUKSI BAWANG MERAH AKIBAT APLIKASI PUPUK ORGANIK CAIR FERMENTASI RUMEN SAPI - Senni Juniawaty Bunga; Yosefina Lewar (Politeknik Pertanian Negeri Kupang, 2009)
The effectiveness of Liquid Organic Fertilizer, Fermented from Cow’s Rumen, effected to onion’s Production. The objectives of this research were to determine: (1) an effectiveness of liquid organic fertilizer; (2) a dosage of liquid organic fertilizer; and (3) an efficiency of the application of liquid organic fertilizer fermented from cow rumen to increase onion’s harvest. This research used a Randomized Group Design with Factorial Pattern using 2 factors. Firstly, a dosage of liquid organic fertilizer fermented from cow rumen (P) that is using some levels: 0, 8, 16, 24, and 32 milliliter/liter clean water. Secondly, the way of fertilizer application (A): by showering to soil media, and by spraying to all of the onion leaves. Analyses of the onion components were made for onions diametric and the weight of dry and wet union. Analyses were made also for the fertilizer nutrition and for the nutrient-rich soil before and after onions were planted. All analyses were performed in duplicate and the data were calculated based on multivariate analyses and were continued to Duncan’s New Multiple Range Test (DMRT) 5%.The result showed that liquid organic fertilizer fermented from cow’s rumen increased onion productivities especially in onion weight (dry and wet matter) and onion diametric. The variation of liquid organic fertilizer dosages (8, 16, 24, and 32 milliliter/liter clean water) did not affect significantly to onion production. Moreover, fertilizer application by drenching to the soil more efficient than by spraying to the onion leaves.Keywords: Liquid Organic Fertilizer, Cow Rumen, Fermented, Onion